Effect of Harvesting States on the Quality of Tomato (Lycopersicon esculentum Mill CV. Avinash-2, Hybrid) - Karki, D. B. (Tribhuvan University Journal, 2010)
Tomatoes harvested at four maturity stages (viz. mature-green, breaker, turning and pink) were washed with 100ppm chlorinated water, sorted and ripened at ambient conditions (20-30°C and 76-85% realtive humidity (RH)). The physico-chemical characteristics of unripe and ripe tomatoes were determined. Key words: Chemical characteristics; Harvesting stages; Ripening; Sensory quality Tribhuvan University Journal Vol. XXV, No. 1, 2005 Page:143-147 Uploaded date: 26, September, 2010